Modeling and Analysis of Multiconductor Transmission Lines by Distributed Transfer Function Method - Yang, Bingen (Journal of Electronics and Electrical Engineering, 2024)
Multiconductor transmission lines (MCTLs) have various applications in electrical engineering. In modeling and analysis of MCTLs, which are described by a set of coupled partial differential equations, most existing methods rely on approximation or discretization. For high-speed high-frequency applications, accurate analytical methods are always desirable. Such a method, however, is not currently available for complex MCTLs. This paper presents an innovative analytical method for modeling and analysis of MCTLs with various configurations. The proposed method, which is called the Distributed Transfer Function Method, is capable of delivering closed-form analytical solutions for complex MCTLs, in both the frequency domain and the time domain. One highlight of the proposed method is that it gives exact and closed-form solutions for branched transmission lines for the first time. The accuracy, efficiency, and high-frequency utility of the method is demonstrated in numerical examples.